Impatiens courtallensis (Balsaminaceae), a new species of Impatiens from Western Ghats, Tamil Nadu, India - R, Ramasubbu; G, Manikandan; P, Mehalingam; Ag, Pandurangan (Phytotaxa, 2015)
Impatiens courtallensis, a new species from Tamil Nadu, India is newly described and illustrated. This species is characterized by having typical opposite deccusate leaves, minute flower (≤4mm across), milky white, boat shaped lower sepal with outwardly curved tip, minute spur, seeds with prominent caruncle and typical squarish pollengrains. This combination of characters makes determining the relationships of I. courtallensis difficult.